Antimicrobial finishing of polypropylene fabric using bioactive nanogels. Issue 4 (21st February 2023) - Verma, Chetna; Somani, Manali; Rajput, Vishav; Bhan, Surya; Nonglang, Flavius Phrangsngi; Lyngdoh, Antonia; Rymbai, Ridashisha; Gupta, Bhuvanesh
Abstract: Antimicrobial polypropylene (PP) was developed by plasma functionalization and subsequent immobilization of chitosan (CS)‐chlorhexidine (CHX) nanogels as the bioactive component. Oxygen plasma was used to create a hydrophilic surface monitored by water drop interaction with the fabric surface. CS nanogels were prepared by the ionic gelation method. The characterization of the nanogels was carried out by transmission electron microscopy (TEM) and energy dispersive X‐ray microanalysis (EDX). The functionalized fabric exhibited excellent antimicrobial nature against S. aureus and E. coli microbes. The animal studies involving mice showed that the material exhibited excellent biocompatibility in contact with the skin. There was no evidence of inflammatory cells in the histopathology. This investigation suggests that the fabric has enormous potential as infection‐resistant material in applications such as wet wipes. Abstract : PP has been functionalized by oxygen plasma to create a hydrophilic surface. The bioactive nanogels of chitosan (CS)‐chlorhexidine (CHX) immobilized to develop antimicrobial fabric surfaces. The biofunctional PP surface is active against gram‐negative and gram‐positive bacteria.